2018
DOI: 10.1158/0008-5472.can-17-3835
|View full text |Cite
|
Sign up to set email alerts
|

Flightless-I Blocks p62-Mediated Recognition of LC3 to Impede Selective Autophagy and Promote Breast Cancer Progression

Abstract: p62 is a receptor that facilitates selective autophagy by interacting simultaneously with cargoes and LC3 protein on the autophagosome to maintain cellular homeostasis. However, the regulatory mechanism(s) behind this process and its association with breast cancer remain to be elucidated. Here, we report that Flightless-I (FliI), a novel p62-interacting protein, promotes breast cancer progression by impeding selective autophagy. FliI was highly expressed in clinical breast cancer samples, and heterozygous dele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Reduced levels of Flii expression, both genetically and using Flii neutralising antibodies, improves skin repair and regeneration in both small and large animal models of healing 7,8,1012 . Studies have identified Flii as a repressor of estrogen receptor signalling and apoptosis suggesting roles in promotion of both skin cancer and breast cancer progression 1315 . In contrast, Flii positively influences tissue regeneration in the context of Wnt signalling pathways during hair follicle regeneration and claw and digit tip regeneration 16,17 illustrating the diverse roles of this cytoskeletal protein.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced levels of Flii expression, both genetically and using Flii neutralising antibodies, improves skin repair and regeneration in both small and large animal models of healing 7,8,1012 . Studies have identified Flii as a repressor of estrogen receptor signalling and apoptosis suggesting roles in promotion of both skin cancer and breast cancer progression 1315 . In contrast, Flii positively influences tissue regeneration in the context of Wnt signalling pathways during hair follicle regeneration and claw and digit tip regeneration 16,17 illustrating the diverse roles of this cytoskeletal protein.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with our observations, previous investigations found that the GH1 truncated human Fli-I, GH26 did not influence the level of steady-state pyrenyl fluorescence suggesting the critical importance of GH1 in actin interaction ( Arora et al, 2015 ). Also, the human Fli-I protein carrying the E586K mutation in the GH1 domain failed to coimmunoprecipitate with actin in 293T cells ( He et al, 2018 ). Based on these considerations the GH1 domain of Fli-I is likely to be the main actin-binding site of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that downregulation of gelsolin proteins counteracts cancer cell invasion in vitro [64], however in cSCC, gelsolin and Flii have been the most studied to-date. Gelsolin over-expression has been shown to promote cell growth and motility in oral SCC [64,65], while Flii, through its effects on apoptosis, has been linked to promotion of breast cancer progression and invasion and progression of cSCC [23,66]. Flii is an important regulator of cell adhesion, migration and proliferation and a number of previous studies have described the role of Flii protein in wound healing and demonstrated the therapeutic effect of Flii neutralizing antibodies (FnAb) in acute and chronic wounds, skin blistering diseases and inflammatory skin conditions [25,32,[67][68][69][70][71][72].…”
Section: Actin Remodeling: Tropomyosin Flightless I and Podoplaninmentioning
confidence: 99%
“…Actin remodeling proteins have long been implicated in cSCC, as a dysregulated actin cytoskeleton and an aberrant tumor microenvironment is a hallmark of aggressive cSCC [11,93]. One particular actin remodeling protein, Flightless I (Flii), has been identified as a tumor promoter with transcriptional activity in colorectal, breast and hepatocellular carcinoma cell lines [66]. However, recent studies have also shown that Flii is significantly increased in human and mouse cSCC tissue samples, while secreted Flii is elevated in the sera of patients with cSCC and is increased in different cSCC cell lines established from human primary, recurring and metastatic cSCC as well as immortalized keratinocytes [23].…”
Section: Therapeutic Approaches Targeting Actin Cytoskeletal Regulatomentioning
confidence: 99%